Effects of Different Modification Methods on the Functional Properties and Structure of Chlorella Protein - HOU Yu-xin; LI Shi-chang; ZHANG Chen; DING Hao; LI Bing-qian; GONG Ming-gui (Liang you shipin ke-ji)
The study employed three methods—odium tripolyphosphate method, neutral protease method, and ultrasonic treatment to modify the Chlorella protein in this paper. The investigation focused on changes in particle size, zeta potential distribution, antioxidant activity, functional properties, thermal stability, and structural characteristics before and after modification. The analysis revealed that compared to unmodified Chlorella protein, all three modification methods significantly reduced particle size and zeta potential. Additionally, significant improvements were observed in solubility, emulsification, emulsion stability, microstructure, and thermal stability. Overall, all three modification methods effectively improved the Chlorella protein. However, the sodium tripolyphosphate method showed only slight improvement in hydrophobicity and fluorescence intensity, with no significant overall improvement observed. The neutral protease method exhibited the most significant improvements in antioxidant activity, water-holding capacity, oil-holding capacity, thermal stability, and secondary structure of the Chlorella protein. For instance, the ABTS free radical scavenging rate increased from 22.95% to 35.72%, and the thermal stability improved by 11.48 ℃ compared to the control. The ultrasonic method significantly increased the solubility of Chlorella protein from 23.56% to 69.66%, emulsification from 70.29 m2/g to 95.25 m2/g, and emulsion stability from 10.74 min to 39.47 min. Additionally, reductions in particle size and improvements in zeta potential were observed.